Desafíos de la conservación del mangle en el Antropoceno - Lugo, Ariel E.; Medina, Ernesto; McGinley, Kathleen (Instituto de Ecología, A.C., 2014)
Issues and Challenges of Mangrove conservation in the AnthropoceneThis essay addresses the conservation issues facing mangroves in the Anthropocene, defined as the era of human domination over theworld. We review the laws, policies, international agreements, and local actions that address the conservation of mangrove forests in theNeotropics and relate them to the Anthropocene. Collaboration between governments, non-governmental organizations, and communitiesthat depend on mangroves for their livelihood will be critical in the Anthropocene. The essay also reviews recent developments inmangrove ecology and ecophysiology that enlighten how mangroves might respond to changes in temperature and rainfall, sea level rise,and other anthropogenic and natural disturbances. Mangroves in the Anthropocene will also face changes in their species compositiongiven the current movement of mangroves species across continental barriers as a result of human activity. These trends will lead to novelmangrove forests and in some cases expand the range of mangroves worldwide. The solution to mangrove persistence in the Anthropoceneis not to isolate mangroves from people, but to regulate interactions between mangroves and humans through effective management.We will also have to expand the scope of the ecological analysis of mangrove ecosystems to include the social forces converging on themangroves through an analytical approach that has been termed Social Ecology.